Divided Legacy : The Partition in Selected Novels of India, Pakistan and Bangladesh / Niaz Zaman. - Zaman, Niaz (Oxford University Press, 2000)
This is perhaps the first book to analyse partition novels in three major languages of the subcontinent: English, Bangali and Urdu. The book is thus an important addition to the numerous writings that have appeared in recent years on an event that not only created two nation states but also affected the psyche of the people who had been divided.